Wykonywanie rodka wychowawczego w postaci skierowania do orodka kuratorskiego z perspektywy kuratorw sdowych - Beata Goworko-Składanek; Tomasz Prymak (Probacja, 2023)
The catalog of educational measures provided by law and applied in juvenile proceedings includes, among others, referral to an attendance centre a facility that provides educational, resocialisation, therapeutic, preventive or control measures for minors. The professional guardians/probation officers who organize the work in the centres confirm that the described measure plays an extremely important role in the process of preventing criminal acts and manifestations of demoralization among minors. It is a non-custodial educational measure which plays an extremely important role in the process of resocialization and whose potential is not fully exploited. The aim of the text is to propose legislative changes aimed at giving this form of resocialization influence the character of a sui generis measure, with a broadened catalogue of competences. The analysis is based on the current legislation, as well as on the results of the author's nationwide research conducted in a group of 32 professional probation officers working in probation centres, aimed at recognizing the specificity of work in these institutions.